Forced disappearances by non-state actors: The case laws of the Inter-American Court of Human Rights - Pietro Sferrazza-Taibi (Íconos)
The goal of this work is to analyze the attribution standards employed by the Inter-American Court of Human Rights (IACHR) in order to account for the State’s responsibility in the forced disappearances perpetrated by non-state actors. This article initially focuses on the classification of perpetrators of disappearances. It then addresses the IACHR sentences about forced disappearances perpetrated by non-state actors who committed these acts with the support, authorization and acquiescence of the State. This article also analyzes the laws about disappearances perpetrated by non-state actors with no connections to the State. In this manner, this work identifies the stages of the law superseded by the IACHR and analyzes the content of the attribution standards employed. Therefore, besides presenting a description of the state in question, this research outlines critical contributions of the path the IACHR followed in order to guide the interpretation of the standards of similar cases and to hypothesize about the cases the IACHR did not address.